Structure of the barents sea from seismic refraction - Renard, V.; Malod, J. (North-Holland Publishing Company, Amsterdam, 1974)
The Barents Sea is underlain by a thick (up to 5 km) sedimentary basin. Seismic refraction has outlined four main velocity discontinuities which have been correlated with geological units on the basis of the geological history of the region. The basin is underlain by a crystalline basement, the nature of which cannot be determined on the basis of seismic velocity alone. Metamorphosed Paleozoic units (velocities around 5-4 km/sec) lie over this basement. Their thickness is not well established but appears to reach 1 or 2 km in some cases. A very distinct and thick (up to 2.5 km) layer (4.1 km/sec) is found almost everywhere and is thought to correspond to a major discontinuity at the end ot the Paleozoic. This discontinuity is followed by a variable velocity layer (2.4-4 km/sec, up to 1.2 km thick) which includes Mesozoic and Cenozoic sediments and is limited to the south of the Barents Sea. The absence of thick Tertiary deposits support the idea that the Barents shelf was emergent at that time. Recent low-velocity sediments are found close to the shelf edge. [NOT CONTROLLED OCR]